2022
DOI: 10.7759/cureus.28609
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for the Improvement of Comorbid Depression Symptoms in Diabetic Patients: A Systematic Review

Abstract: Diabetes mellitus and depression are chronic debilitating disorders and can occur comorbidly. They are thought to be linked not only through environmental and behavioral factors but through molecular mechanisms as well. Antidepressant medication and psychological therapy, standard treatments for depressive symptoms in Type 2 diabetes mellitus, are linked to high rates of treatment failure and nonadherence; therefore, understanding the molecular mechanisms linking diabetes and depression could lead to discoveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Lastly, the lack of data about medication use may also be a major limitation. Metformin, a major medication for type 2 diabetes, has been proposed to treat comorbid depression and diabetic patients [ 68 ]. Several studies have suggested that antidepressants can induce (Mirtazapine (SNRI), TCAs amitriptyline and nortriptyline) and reduce (selective Serotonin re-uptake inhibitors) weight gain as a side effect [ 69 , 70 , 71 ], although results vary depending on the duration of exposure and types of medication [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the lack of data about medication use may also be a major limitation. Metformin, a major medication for type 2 diabetes, has been proposed to treat comorbid depression and diabetic patients [ 68 ]. Several studies have suggested that antidepressants can induce (Mirtazapine (SNRI), TCAs amitriptyline and nortriptyline) and reduce (selective Serotonin re-uptake inhibitors) weight gain as a side effect [ 69 , 70 , 71 ], although results vary depending on the duration of exposure and types of medication [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population of diabetic patients, there is no clear consensus on whether anti-diabetic agents reduce depression, with some supporting metformin or pioglitazone use but others not finding consistent associations, and positive findings not correlating with HOMA-IR. 37,38 A pilot trial of 19 adolescents and 25 adults with PCOS found that after 3 months of metformin 1,500 mg/day, the severity of depression symptoms as measured by the Beck Depression Inventory-II (BDI-II) decreased significantly in both the adolescent and adult groups, with 70.5% of patients having a decrease of 2 points or more (p < 0.001). 39 However, prior meta-analyses have not shown improvements in PCOS quality of life with the addition of metformin to lifestyle interventions.…”
Section: Insulin Sensitizing Agentsmentioning
confidence: 99%
“…59,60 A randomized clinical trial of 72 women with PCOS assigned to 16 weeks of acupuncture, exercise, or control groups found reductions in Montgomery Asberg Depression Rating Scale (À1.00 AE 8.07) and Brief Scale for Anxiety (À1.74 AE 7.88) in the acupuncture group at week 32. 27 A secondary analysis of a pilot randomized trial in China conducted over 16 weeks in 54 women with PCOS found that those in the electroacupuncture arm had significantly decreased depression scores as measured by the Zung-SDS (median: 33 [IQR: [31][32][33][34][35][36][37][38][39][40] vs. 42 [IQR: 37-50], p ¼ 0.004) and significantly improved total Chinese Quality of Life scores (median: 198 [IQR: 175-210] vs. 176 [IQR: 173-187], p ¼ 0.023). 61 Dietary modifications targeting insulin-sensitizing and inflammatory pathways have also been evaluated.…”
Section: Complimentary Medicine Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Preclinical and clinical data suggest a potential role of metformin in improving depressive symptoms: however, the data is, as yet, inconclusive. 23 Dyslipidemia patients are at higher risk of developing cardiovascular diseases (CVD), and patients with CVD are at higher risk for depression. 24…”
Section: Introductionmentioning
confidence: 99%